THE ALL-INSIDE ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION WITH FIBER-LOOP AUGMENTATION - Vu, Anh Dung; Tran, Quang Dung; Pham, Ngoc Thang (Tạp chí Y Dược học Quân sự (Vietnamese issues), 2023)
Objectives: To evaluate the functional outcomes in patients who underwent anterior cruciate ligament (ACL) reconstruction with fiber-loop augmented to reinforce the ligament, acting as a secondary stabilizer. Methods:A retrospective study was conducted on 25 patients who underwent the all-inside ACL reconstruction with the addition of fiber-loop inside the ACL graft in the Department of Joint Surgery, Military Hospital 103, from August 2022 to August 2023. Patients were evaluated pre-operatively and finally post-operatively via the Lachman test, Pivot shift test, and Lysholm score. Results: The mean follow-up was 9.84 months; the mean age was 33.04 ± 9.95 years. 24 patients (96%) were post-operatively Lachman negative. The pivot-shift test showed 96% of patients absent or glide after surgery. The Lysholm knee score at the last visit was good and very good in 96% of the patients; the mean score was 92.56 ± 4,53. Conclusion: This study showed good functional outcomes of arthroscopic ACL reconstruction with fiber-loop augmentation to reinforce the ligamental graft. There is a need for more comparative studies with longer follow-ups and large sample sizes.